Subacute aortic prosthetic mechanical valve thrombosis complicated with acute coronary syndrome - ÇİNÇİN, AHMET ALTUĞ; ÖZBEN SADIÇ, BESTE; ATAŞ, HALİL; TİGEN, MUSTAFA KÜRŞAT (W B SAUNDERS CO-ELSEVIER INC, 2018)
A prosthetic valve thrombosis (PVT), which is a potentially fatal complication, refers to the presence of non-infective thrombotic material on a prosthetic valve apparatus, interfering with its function. Possible complications of a PVT include transient neurologic embolic events, cardiac arrest due to a stuck valve prosthesis, and cardio-embolic myocardial infarction (MI). The choice of treatments, including a redo surgery, a percutaneous coronary intervention (PCI), and a fibrinolysis with PVT or MI dosages, depends on the patient's dinical and hemodynamic status and thrombotic burden involving the prosthetic valve and surrounding tissues. An early post-operative mechanical valve thrombosis is associated with increased risks due to the need for unforeseen early redo surgery complications and excessive bleeding risk in case of thrombolytic therapy usage. Here, we present a fifty-seven-year old female patient who was admitted to the emergency department with the complaint of acute chest pain seven days after an aortic prosthetic mechanical valve implantation. The clinical presentation was consistent with ST segment elevated MI and echocardiography revealed a large mass on the recently implanted prosthetic aortic valve. Valvular thrombotic complications after heart valve replacement operations are associated with high morbidity and mortality rates. Efficient and urgent treatment is necessary. Considering the clinical status of the patient, we preferred fibrinolytic therapy rather than PC1 or surgery. The aim of this case report was to show the efficiency and safety of low-dose slow-infusion fibrinolytic therapy in PVT complicated with acute coronary syndrome. (C) 2018 Elsevier Inc. All rights reserved.
Keywords: Aortic prosthetic valve; Cardio-embolic myocardial infarction; Mechanical valve thrombosis; Thrombolytic therapy; VALVULAR HEART-DISEASE; MANAGEMENT; TRIAL